Budget-Impact Analysis of Health Care Interventions A Practical Guide - Mauskopf, Josephine; Earnshaw, Stephanie R.; Brogan, Anita; Wolowacz, Sorrel; Brodtkorb, Thor-Henrik.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2017)
The first of its kind for budget-impact analysis, this comprehensive guide provides clear and concise instructions for evaluating the impact that new pharmaceuticals will have on the budget for a specific jurisdiction. The book demonstrates how to create a budget-impact analysis using a simple six-step process that is consistent with current guidelines for these analyses. Examples and exercises for each chapter afford an opportunity to practice the six-step process in practical applications. The book progresses from a framework for budget impact analyses to an in-depth review of components and how to develop and present these in software applications and reports. Critical considerations such as uncertainty analysis and validation, and considerations for alternate interventions, such as vaccines and diagnostics, are also covered. This book is a (3z(Bmust have(3y (Bfor the builder and budget holder, with builders benefiting from instructions to identify and estimate all necessary variables and budget holders receiving a guide to what should be included in the analyses they assess.s
1. Introduction to Budget-Impact Analysis -- 2. Determining the Analytic Framework -- 3. Estimating the Diagnosed, Treated, and Eligible Population -- 4. Estimating the Treatment Mix -- 5. Estimating Treatment-Related Costs -- 6. Estimating Condition-Related Costs -- 7. The Computing Framework and Calculations -- 8. Uncertainty Analysis -- 9. Validation -- 10. Software and Computer Interface -- 11. Reporting Budget-Impact Analyses -- 12. Additional Pragmatic Topics -- 13. Alternative Interventions -- 14. Creating Your Own Budget-Impact Analyses Today and Tomorrow.
Keywords: Medicine; Health informatics; Medical research; Pharmacy management; Quality of life; Medicine & Public Health; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health informatics